Investigation of the Impact of Large-Scale Wind Power and Solar Power Plants on a Vietnamese Transmission Network - Ngo Minh Khoa; Nguyen Thi Hai Van; Le Kim Hung; Doan Anh Tuan (My University, 2022)
Investigation of the Impact of Large-Scale Wind Power and Solar Power Plants on a Vietnamese Transmission Network
Keywords: Năng lượng tái tạo; Lưới điện Việt Nam; Truyền tải điện